2012
DOI: 10.1523/jneurosci.0925-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Imaging of Cerebral β-Amyloidosis with Extended-Focus Optical Coherence Microscopy

Abstract: We demonstrate label-free imaging of cerebral ␤-amyloidosis ex vivo and in a living mouse model of Alzheimer's disease using extendedfocus Fourier domain optical coherence microscopy (xfOCM). xfOCM provides 3D, high-resolution images of individual ␤-amyloid plaques in the brain parenchyma and vasculature and requires no staining of the Alzheimeric sample under investigation. xfOCM also opens the possibility to perform minimally invasive studies of ␤-amyloid pathology in vivo, without the use of labeling method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 25 publications
3
46
0
Order By: Relevance
“…Cerebral amyloid-β (Aβ) amyloidosis, an early and critical biomarker for Alzheimer’s disease, has been visualized ex vivo and in vivo in Alzheimeric mouse models with OCM [115]. Amyloid plaques were detected up to 500 µm below the cortical surface.…”
Section: Oct In Brain Imagingmentioning
confidence: 99%
“…Cerebral amyloid-β (Aβ) amyloidosis, an early and critical biomarker for Alzheimer’s disease, has been visualized ex vivo and in vivo in Alzheimeric mouse models with OCM [115]. Amyloid plaques were detected up to 500 µm below the cortical surface.…”
Section: Oct In Brain Imagingmentioning
confidence: 99%
“…Similar methods were used to study microischemia because of repeated cocaine administration 15 and to generate images of vasculature for longitudinal image registration in a mouse model of cerebral β-amyloidosis. 16 In this paper, we present an OCT platform that enables longitudinal and quantitative monitoring of both global flow and microvascular flow patterns during chronic cerebral hypoperfusion, imaged for up to nine time points in the same animal over 1 month. In particular, the system parameters, animal model, and scanning protocols were optimized to enable selective imaging of red blood cell (RBC)-perfused capillaries.…”
Section: Introductionmentioning
confidence: 99%
“…The OCM was used to image individual axons and unveil the myeloarchitecture in the cortex (Srinivasan et al, 2012; Leahy et al, 2013). Previous studies on brain and peripheral nerves using OCM have reported close correlations with histology (Arous et al, 2011; Bolmont et al, 2012; Magnain et al, 2013). Therefore, the method we propose (SOCS) has the potential to bridge multi-modality investigations on the central and peripheral nervous systems to construct a hierarchal view of neuroanatomical connections from molecular to system levels, thus opening important opportunities for systematic studies on brain mapping and neural disorders.…”
Section: Discussionmentioning
confidence: 72%